La participación de la iglesia católica en el control del espacio en medio de la creación de un país llamado Costa Rica, 1850-1920 - Sandí Morales, José Aurelio (2011)
This essay analyzes the collaboration of the Catholic Church with the Costa Rican State between the foundations of the Diocese of San José until 1920. lt shows how the Church helped to control, watch and take over the geographical space of Costa Rica and individual living in that land. It also studies mechanisms of control the Catholic Church carried out in this process.